The silence of the archive - Thomas, David 1950-; Fowler, Simon; Johnson, Valerie (Archivist) (Principles and practice in records management and archives, 2017)
Records and archives, whether maintained by individuals, organizations, or community groups, are important sources that provide evidence of, and information about, the course of their creators and the environment in which those actions occurred. But at time incompleteness can be frustrating to those who seek to use them. The authors explore the societal impact of records and archives, and the consequences that result when records are absent or uniformative. They look at the ways in which the lack of comprehensive record keeping creates "silences" which, though unsettling to some, are sometimes inevitable.